The path forward: 2015 International Children's Tumor Foundation conference on neurofibromatosis type 1, type 2, and schwannomatosis. Issue 6 (24th April 2017) - Blakeley, Jaishri O.; Bakker, Annette; Barker, Anne; Clapp, Wade; Ferner, Rosalie; Fisher, Michael J.; Giovannini, Marco; Gutmann, David H.; Karajannis, Matthias A.; Kissil, Joseph L.; Legius, Eric; Lloyd, Alison C.; et al.
Abstract : The Annual Children's Tumor Foundation International Neurofibromatosis Meeting is the premier venue for connecting discovery, translational and clinical scientists who are focused on neurofibromatosis types 1 and 2 (NF1 and NF2) and schwannomatosis (SWN). The meeting also features rare tumors such as glioma, meningioma, sarcoma, and neuroblastoma that occur both within these syndromes and spontaneously; associated with somatic mutations in NF1, NF2, and SWN. The meeting addresses both state of the field for current clinical care as well as emerging preclinical models fueling discovery of new therapeutic targets and discovery science initiatives investigating mechanisms of tumorigenesis. Importantly, this conference is a forum for presenting work in progress and bringing together all stakeholders in the scientific community. A highlight of the conference was the involvement of scientists from the pharmaceutical industry who presented growing efforts for rare disease therapeutic development in general and specifically, in pediatric patients with rare tumor syndromes. Another highlight was the focus on new investigators who presented new data about biomarker discovery, tumor pathogenesis, and diagnostic tools for NF1, NF2, and SWN. This report summarizes the themes of the meeting and a synthesis of the scientific discoveries presented at the conference in order to make the larger research community aware of progress in the neurofibromatoses.